POETIC TEXTS AND GRAMMAR TRANSFORMATION IN GERMAN LANGUAGE TEACHING - Sattorova, Shakhnoza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
This article examines the role of poetic texts in German language teaching and their significance for the development of grammatical competence. It focuses on how poetic texts can be effectively used to teach German in higher education. The article comprehensively addresses the functions of poetic texts, the criteria for text selection, and the challenges of integrating them into the teaching process. Working with poetic texts not only promotes language skills but also strengthens learners’ cultural awareness and contributes to their holistic development. The aim of the research is to evaluate the effectiveness of poetic texts in expanding vocabulary and promoting intercultural and grammatical competence. The study’s tasks include analyzing the didactic functions of poetic texts, developing criteria for text selection, and identifying difficulties in integrating them into the learning process. The study was conducted using a combination of qualitative and quantitative research methods. These methods included analyzing poetic texts of different genres and conducting didactic experiments with learners. Innovative approaches such as creative writing exercises and discussions were used to analyze the effect of poetic texts on language development. The results show that the use of poetic texts contributes significantly to improving learners’ grammatical competence, particularly through the contextualization of new words. The conclusion is that careful planning and a flexible approach are crucial when selecting and integrating poetic texts. This study highlights that poetic texts are highlyeffective not only as a means of language teaching but also for cultural education and creative development.